2011
DOI: 10.1038/ismej.2011.183
|View full text |Cite
|
Sign up to set email alerts
|

Verminephrobacter eiseniae type IV pili and flagella are required to colonize earthworm nephridia

Abstract: The bacterial symbiont Verminephrobacter eiseniae colonizes nephridia, the excretory organs, of the lumbricid earthworm Eisenia fetida. E. fetida transfers V. eisenia into the egg capsule albumin during capsule formation and V. eiseniae cells migrate into the earthworm nephridia during embryogenesis, where they bind and persist. In order to characterize the mechanistic basis of selective tissue colonization, methods for site-directed mutagenesis and colonization competence were developed and used to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Verminephrobacter symbionts in the earth worm also pass through a narrow entrance known as a "colonization duct" during host embryogenesis [26]. Notably, flagella motility is also pivotal for the symbiont colonization in the earthworm system [27]. We highly expect that an unforeseen motile mechanism will be found to play a pivotal role in these symbiotic associations, possibly revealed by an advanced microscopic technology such as a TIRFM.…”
Section: Discussionmentioning
confidence: 99%
“…Verminephrobacter symbionts in the earth worm also pass through a narrow entrance known as a "colonization duct" during host embryogenesis [26]. Notably, flagella motility is also pivotal for the symbiont colonization in the earthworm system [27]. We highly expect that an unforeseen motile mechanism will be found to play a pivotal role in these symbiotic associations, possibly revealed by an advanced microscopic technology such as a TIRFM.…”
Section: Discussionmentioning
confidence: 99%
“…Type IVa pili were also found in S. alvi, as were type I secretion system RTX proteins and YadA-like adhesins. These features are best known for their roles in pathogenesis, but in gut symbionts, they may instead function in mutualistic interactions (30)(31)(32). Capsular polysaccharides, RTX proteins, type IV pili, T6SS, and adhesins can take part in biofilm synthesis and modulation (33)(34)(35)(36)(37)(38), reinforcing the idea that biofilm formation is a key process in bee gut colonization (15,16).…”
Section: Strains Wkb1mentioning
confidence: 94%
“…Our analysis, which used the alignment program MAUVE (Darling et al, 2010), was based on the assumption that, if a gene is not present in the genomes of all 12 of the strains that were isolated from squid light organs, then it is unlikely to be critical for light-organ symbiosis. For instance, type-4 pili (T4P) are a class of surface structures often associated with pathogenic or beneficial microbial colonization of host tissue (Craig et al, 2004;Dulla et al, 2012), and 10 distinct T4P gene clusters have been identified in V. fischeri strain ES114 (Ruby et al, 2005). Some of these putative pilus proteins (that is, MshA, PilT and PilA2) have been linked previously to the colonization process Ariyakumar and Nishiguchi, 2009;Chavez-Dozal et al, 2012).…”
Section: Mauve-gene Distributionmentioning
confidence: 99%